Hypo- vs. normofractionated radiation therapy in breast cancer: A patterns of care analysis in German speaking countries - Mayinger, M.; Straube, C.; Habermehl, D.; Duma, M. N.; Combs, S. E. (Reports of Practical Oncology and Radiotherapy, 2020)
Aim and background: To assess the use of hypofractionated (HG-RT) versus normofractionated radiation therapy (NF-RT) in Breast Cancer in German speaking countries. Materials and methods: Between July 2017 and August 2017, an email-based survey was sent to all 1408 physicians that are members of the German Society of Radiation Oncology (DEGRO). The survey was completed by 180 physicians including 10 private practice owners and 52 heads of departments. The majority (82.1%) of the participants had >15 years of experience in radiation therapy (RT). Results: The majority (83.9%) of the heads of the departments agreed on using the normofractionated regimen of RT as standard treatment for breast cancer. Several physicians were skeptical about HF-RT with 6.5% of the heads refusing to use HF-RT. 40.3% of the departments had not seen the new German guidelines suggesting HF-RT as the standard treatment for all patients as positive or merely adopted a neutral position toward the guidelines (33.9%). The main points of criticism were increased side effects, an impaired toxicity profile and insufficient data. Most departments (46.8%) that perform HF-RT do so in an individual based manner. Conclusions: HF-RT remains controversial in German speaking countries. Our data shows that NF-RT remains the predominant method of treatment. HF-RT is only used in a defined group of patients as most German physicians agree that particular patients, especially those at higher risk of RT late effects, may benefit from a less intense, extended fractionation schedule.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Breast cancer; Hypofractionated radiotherapy; Normofractionated radiotherapy; Patterns of care